You would use the Pythagorean theorem and plug it in
Answer:
x = -5, x = -6
Step-by-step explanation:
After canceling common terms from numerator and denominator, there are two factors remaining in the denominator that can become zero. The vertical asymptotes are at those values of x.
![\displaystyle F(x)=\frac{x\frac{2x}{2}}{x(x+5)(x+6)}=\frac{x}{(x+5)(x+6)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20F%28x%29%3D%5Cfrac%7Bx%5Cfrac%7B2x%7D%7B2%7D%7D%7Bx%28x%2B5%29%28x%2B6%29%7D%3D%5Cfrac%7Bx%7D%7B%28x%2B5%29%28x%2B6%29%7D)
The denominator will be zero when ...
x + 5 = 0 . . . . at x = -5
x + 6 = 0 . . . . at x = -6
Answer
i would say Logan’s is the best because he has the most sorry if I’m wrong. And I’m not good at Englis.
Answer:
schools and other services